2018
DOI: 10.1371/journal.ppat.1007248
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella Typhimurium effector SseI inhibits chemotaxis and increases host cell survival by deamidation of heterotrimeric Gi proteins

Abstract: Salmonella enterica serotype Typhimurium (S. Typhimurium) is one of the most frequent causes of food-borne illness in humans and usually associated with acute self-limiting gastroenteritis. However, in immunocompromised patients, the pathogen can disseminate and lead to severe systemic diseases. S. Typhimurium are facultative intracellular bacteria. For uptake and intracellular life, Salmonella translocate numerous effector proteins into host cells using two type-III secretion systems (T3SS), which are encoded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 67 publications
2
17
0
2
Order By: Relevance
“…Typhimurium‐infected macrophages in a T3SS‐independent manner. Brink et al () recently reported that Ssel, an SPI‐2 effector, induces AKT phosphorylation by activating the G protein in macrophages. Here, we tested whether S .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Typhimurium‐infected macrophages in a T3SS‐independent manner. Brink et al () recently reported that Ssel, an SPI‐2 effector, induces AKT phosphorylation by activating the G protein in macrophages. Here, we tested whether S .…”
Section: Resultsmentioning
confidence: 99%
“…Intriguingly, phosphorylation of another mTOR substrate, S6K1, and its downstream molecule, S6, is not decreased but rather increased, whereas the status of ULK1 S757 phosphorylation is not reported (Tattoli, Sorbara, Vuckovic, et al, ). Brink et al () found that S . Typhimurium infection of bone marrow‐derived macrophages leads to increased AKT and S6K1 phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it seems that manipulating the antigen presentation capability of antigen presenting cells is another important strategy of pathogens for suppressing and escaping the host immune responses [224]. SseI has been shown to block the migration of DCs to lymphocytes [225]. Moreover, the major histocompatibility complex (MHC) plays an important role in combating the Salmonella during the later stages of infection [226,227].…”
Section: Escape Of Adaptive Immune Responsesmentioning
confidence: 99%
“…This modification impairs Rho signaling and results in actin cytoskeleton disintegration, blockade of phagocytosis, and death of insect larvae. The second effector domain is a deamidase (PaTox D ) that resembles the type III secreted effector SseI from Salmonella typhimurium (11). It deamidates a catalytic glutamine residue of heterotrimeric G␣ proteins, resulting in the permanent activation of the GTPase signaling molecule (10).…”
mentioning
confidence: 99%